Hubungan antara Dukungan Sosial Teman Sebaya dengan Kesejahteraan Subjektif Pada Siswa Kelas XII di Sekolah Menengah Atas - Salsabila, Zahra; Wijaya, Erik (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the correlation between social support from peers and subjective well-being in class XII students in high school. Social support is a feeling of concern, comfort, self-esteem, or any form of assistance that has been received by an individual from another group or person (Sarafino, 2010). According to Diener (2006), subjective well-being includes all types of evaluations in life that are positive or negative. The participants in this research were 388 students who were in class subjective well-being (PANAS) by Diener (2006). The results of the analysis using the Pearson Correlation technique show that the results of the peer social support variable have a significant and positive relationship with the subjective well-being variable. This can be shown from the value of r (388) = 0.108 and the value of p = 0.033 < 0.05. Next, the researchers conducted a correlation test between the subjective well-being variable and the peer social support variable, which had a significant and positive relationship. This can be shown from the value of r (388) = 0.108 and the value of p = 0.033 < 0.05.